Review of the genus Lanchnophorus (Hemiptera: Heteroptera: Rhyparochromidae) with description of three new species and other nomenclatural changes - Kment, Petr; Carapezza, Attilio; Jindra, Zdeněk; Kondorosy, Előd (Zootaxa, 2017)
The generic name Lanchnophorus Reuter, 1887, deemed for a long time to be unavailable as incorrect original spelling of Lachnophorus (in fact Lachnophorus Distant, 1903 is an unjustified emendation of the former), is restored as a valid name of the genus. Lachnesthus Bergroth, 1915, syn. nov. (new name for the preoccupied Lachnophorus Distant, 1903) is considered junior synonym of Lanchnophorus. The following nomenclatural changes are proposed: Lanchnophorus flavus (Scudder, 1971) comb. nov. = Lachnesthus chinai Scudder, nomen nudum; Lanchnophorus guttulatus Reuter, 1887, comb. restit. = Lachnophorus albidomaculatus Distant, 1913, syn. nov. = Lachnesthus rodriguezensis China, 1925, syn. nov.; Lanchnophorus leucospilus (Walker, 1872) comb. nov.; Lanchnophorus merula (Distant, 1903) comb. nov.; and Lanchnophorus singalensis (Dohrn, 1860) comb. nov. Three new species are described: Lanchnophorus gaoqingae Kment & Jindra sp. nov. from China (Yunnan), Lanchnophorus seminitens Kment & Carapezza sp. nov. from Socotra Island (Yemen), and Lanchnophorus webbi Kondorosy sp. nov. from India: Tamil Nadu. Bibliographies and known distribution of all the included species are reviewed. The following new country and state records are provided: L. flavus from Central African Republic, Ethiopia, Ghana, Mali, Malawi, Niger, Zambia and Zimbabwe; L. leucospilus from China (Yunnan) and Laos, L. merula from India (Kerala/Tamil Nadu) and Thailand; L. singalensis from Angola, Benin, Mozambique, Namibia, Senegal, Sierra Leone, Tanzania, Togo, Uganda, Zambia, Zimbabwe, China (Hainan), Iran (Sistan and Ba-luchestan), Oman, Pakistan, India (Himachal Pradesh, Karnataka, Kerala, Rajasthan), Malaysia, Philippines, and Thailand.